Environmental citizenship in citizen science: a case study of a volunteer toad conservation group in Noordhoek, South Africa - Van Wyk, Sheraine Maud (Rhodes University, Faculty of Education, Department of Education, 2015)
The endangered Western Leopard Toad (Amietophrynus pantherinus) is endemic to the winter-rainfall parts of the Western Cape, areas which are also favoured for human settlement. Residents in the Noordhoek area witnessed many toads being killed on roads during their annual migration to breeding ponds. Concerned citizens mobilised a volunteer group to mitigate this threat to the species. Toad NUTS (Noordhoek Unpaid Toad Savers), a well-established and successful citizen science group is explored as a case study of how environmental citizenship emerges in a citizen science group. This research has three research goals. Firstly to probe the enabling and constraining factors shaping the Toad NUTS practices, secondly to investigate the learning dynamics in the citizen science group and thirdly to understand how participation in citizen science develops environmental citizenship. Practice architectures theory (Kemmis & Grootenboer, 2008) was used to explore how cultural-discursive, economic-material and social-political arrangements shape the practices of the Toad NUTS group. The Toad NUTS group was identified as a community of practice, therefore Lave and Wenger's (1991) communities of practice theory was used to better understand the social learning processes within the group. The Global Citizenship Education international policy document was used to capture the aims of citizenship education as it relates to environmental issues and identifies the competencies that citizenship education initiatives should develop. The practices of the Toad NUTS group were investigated for evidence of the goals and competencies identified in the Global Citizenship Education policy documents of environmental citizenship. Data was generated through documentary research, surveys, a questionnaire, semi-structured interviews and observations. The data was stored, organised and analysed using NVivo data management software in three phases corresponding to the three research goals. With respect to Goal 1, the evidence suggested that there are various shaping arrangements of cultural-discursive, material-economic and social-political configurations which influence Toad NUTS practices. Volunteers must learn to navigate these arrangements in order to successfully implement conservation strategies. The shaping features identified were the WhatsApp group communication system used by volunteers; public awareness and education strategies; equipment, material and funding required for implementing the group's practices; power balances and exchanges between stakeholders in the conservation field; bureaucratic processes and scientist-lay person exchanges. Very important for facilitating social-political connections to various stakeholders, is the membership Toad NUTS enjoys on the Western Leopard Toad Conservation Committee. With respect to Goal 2, four interconnected components of learning were investigated. These were: learning as belonging, learning as doing, learning as meaning-making experience and learning as becoming. Members learn by doing things together like training, patrolling and deliberating problems in the field. They learn by exploring what is collectively known from past and unfolding experiences. Evidence showed that learning deepens as Toad NUTS members perceive their praxis as meaningful and their identities evolve as their knowledge and experience grows. This strengthens members' sense of belonging and identification with the Toad NUTS group. In time the group develops a reputation and the wider community acknowledges the expertise and knowledge that resides with the group. With respect to Goal 3, it was found that volunteers who have a predisposition for environmental citizenship are more likely to join a citizen science group. Although volunteers care about nature and want to make a difference, it is after gaining access to the embedded knowledge and knowledge processes of the citizen science group that they realise meaningful sustainable solutions to the issue(s) that the project is concerned with. It was found that knowledge paired with reasoned practice enables the agency of volunteers to bring about positive and meaningful change in the local environment. If facilitated carefully, citizen science can make positive contributions to the field, in this instance, conservation, while allowing volunteers to exercise environmental citizenship engaging in participative governance with regard to the project.
Keywords: Toad NUTS (Noordhoek, -- South Africa); Environmental education -- South Africa -- Noordhoek; Environmental education -- Citizen participation; Social learning -- South Africa -- Noordhoek; Toads -- Conservation -- South Africa -- Noordhoek; Toads -- Conservation -- Citizen participation